ANALYSIS OF OPERATIONAL MANAGEMENT PERFORMANCE THROUGH APPLICATION OF STANDARD COSTING IN PT. ATLANTIC BIRURAYA - Hidayati, Cholis; Amelia, Ariya (JEA17: Jurnal Ekonomi Akuntansi, 2023)
The purpose of this study to analyze the performance of operational management by evaluating the variance resulting from standard conversion costs and actual conversion costs. The design of this research is to do a case study approach. The data used is the production cost report for the period January to October 2022. In addition, there is historical data regarding packaging purchases and information about the company. The method used in this study is a qualitative method by calculating the conversion cost variance. The results of the study show that there is a favorable variant in the cost of converting finished goods to cups of -Rp. 26,884,087.42, an unfavorable variant in the cost of converting finished goods to bottles of Rp. 24,115,098.18, an unfavorable variant in the cost of converting finished goods to gallons of Rp. 83,162,947. 03. From the results of this study it can be seen how the role of operational management during a series of production processes. There are still obstacles beyond the control of operational management and the lack of evaluation of standard costs on a regular basis causes a number of cost deviations that can be detrimental to the company.